ANALISIS IMPLEMENTASI LAYANAN MOBILE JKN DI RUMAH SAKIT DR. BRATANATA KOTA JAMBI TAHUN 2025 - Alvin Febrian; Adila Solida; Arnild Augina Mekarisce (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the implementation of Mobile JKN services at dr. Bratanata Hospital, Jambi City in 2025. This study uses a qualitative approach with a case study design to explore real conditions in the field. Data were collected through in-depth interviews, observation, and documentation involving key informants, main informants, and supporting informants. The findings indicate that the implementation of Mobile JKN has not been fully optimal. Technical barriers such as system errors, unstable internet connections, and data synchronization issues are still frequently encountered. In addition, non-technical barriers such as low digital literacy among patients and limited human resources also affect service effectiveness. Weak coordination between institutions further complicates the implementation process. These conditions result in increased waiting times, higher patient complaints, and a return to manual service systems. Strengthening infrastructure, improving human resource capacity, and optimizing inter-system integration are necessary to enhance digital health service performance.